Characteristics Of Young Learners.PNG - Almalti, Khadija Suliman (مجلة كلية الاداب, 2022)
The characteristics and skills children possess at school age are enormous and at the same time incredible. Hence, the researchers of this article have decided to describe some of these characteristics because they believe that such characteristics surely contribute positively to the success of children’s foreign language education. The article emphasizes the fact that a teacher of a foreign language has to have enough knowledge about children, their characteristics and their abilities before they meet with them in the classroom. The article also illustrates how an understanding of how children learn will make teaching effective and learning successful. Understanding the child learner’s behaviour and reaction towards what he/she encounters in their surrounding will certainly help language teachers in the task ahead of them. The task of teaching a foreign language to young learners requires enormous time and effort and, above all, preparation. Serious attention and intensive effort to understand the child learner’s characteristics and skills will certainly lead to successful and fruitful achievement of foreign language learning and teaching alike. This article, therefore, presents different learner’s characteristics, but it only focuses on two of them: Fun and play and Learning through doing. In addition, it looks at how these two characteristics are reflected in learning activities and textbooks.